A Comparative Study of Social Network Mining of Massive Open Online Courses to Create an Open Course Module Structure. - Binu Mol T. V. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The review on various online courses, E-learning, Massive Open Online Course (MOOC) gives a static methodology for preparing the content. It gives hardship for the teachers to create a content for a topic. Study on Information and Communication Technology (ICT), Flipped classroom learning and models done to select what type of flipped classroom to be followed. Technologies present for Flipped classroom reveals which technology can be done in the case. Data mining techniques for e-learning studied to select which web mining method to select creating contents. Study on IoT sensors done to how to use IoT in selecting content for course for a module and language for creating source code and algorithm. Analysis of visualization tools for IoT enabled to select the tool for development. The study helps to initiate a method to create open course module structure from social network mining for e-learning which will help educators to easily create e-learning modules.